Safety management in times of crisis: Lessons learned from a nationwide status-analysis on German intensive care units during the COVID-19 pandemic - Schmidt, Michelle; Lambert, Sophie Isabelle; Klasen, Martin; Sandmeyer, Benedikt; Lazarovici, Marc; Jahns, Franziska; Trefz, Lara Charlott; Hempel, Gunther; Sopka, Saša (Frontiers in Medicine, 2022)
Background: The status of Safety Management is highly relevant to evaluate an organization’s ability to deal with unexpected events or errors, especially in times of crisis. However, it remains unclear to what extent Safety Management was developed and sufficiently implemented within the healthcare system during the COVID-19 pandemic. Providing insights of potential for improvement is expected to be directional for ongoing Safety Management efforts, in times of crisis and beyond. Method: A nationwide survey study was conducted among healthcare professionals and auxiliary staff on German Intensive Care Units (ICUs) evaluating their experiences during the first wave of the COVID-19 pandemic. Error Management and Patient Safety Culture (PSC) measures served to operationalize Safety Management. Data were analysed descriptively and by using quantitative content analysis (QCA). Results: Results for n = 588 participants from 53 hospitals show that there is a gap between errors occurred, reported, documented, and addressed. QCA revealed that low quality of safety culture (27.8 %) was the most mentioned reason for errors not being addressed. Overall, ratings of PSC ranged from 26.7 % to 57.9 % positive response with Staffing being the worst and Teamwork Within Units being the best rated dimension. While assessments were going in the same direction, medical staff rated PSC on ICUs more positively in comparison to nursing staff. Conclusion: The status-analysis of Safety Management in times of crisis revealed relevant potential for improvement. Human Factor plays a crucial role in the occurrence and the way errors are dealt with on ICUs, but systemic factors should not be underestimated. Further intensified efforts specifically in the fields of staffing and error reporting, documentation and communication are needed to improve Safety Management on ICUs. These findings might also be applicable across nations and sectors beyond the medical field.